Whose 'Lost Ground'? Facets of Outsiderhood. Issue 1 (2nd January 2020) - Dimitriu, Ileana
Abstract : The article considers the concept of 'home' and its experiential application in relation to Michiel Heyns's novel, Lost Ground . A prize-winning novel in South Africa, Lost Ground has taxed interpretation. Is it a detective novel, a novel of 'gay' relationships, or a novel of oblique rather than direct political observations on 'post-apartheid' South Africa? I argue that the novel is all the above, but tangentially. More centrally, I argue that Lost Ground explores commitment and non-commitment to both a home place and a place of exile; that Heyns is too subtle a novelist to promote an either/or response to a situation which, at least in the narrative, subjects despair to a muted redemption. If the protagonist does not find a home on his 'home visit, ' neither does he find equanimity in his thoughts of a return to London. Yet, his experience in his brief return to the town of his earlier life grants him fresh insight into his own vulnerability.